Assessment of the plant species diversity in Cilician fir (Abies Cilicica Carr.) forest in Cedar and Fir Reserve_ Syria - حكمت عباس; وائل علي; أحمد محمود; بشار طوبو (Latakia University Journal -Biological Sciences Series, 2022)
Plant species diversity of Cilician fir forest within the Cedar and Fir Reserve in Lattakia Governorate – Syria was assessed based on trees inventories conducted on 46 sample plots of 400 m2 covering the whole forest area. Diversity was estimated using Species Richness Shannon-Wiener index and evenness index, whereas the similarity between different slopes of studied area was calculated using Jaccard index. A total of 25 plant species belonging to 19 genera and 13 families were recorded from a total area of 978 ha. Rosaceae was the dominant family in the forest with 6 species followed by Fagaceae with 5 species. Species with highest relative coverage were Abies Cilicica L. (46.4%), Carpinus orientalis Mill. (5.9%) and Ostrya carpinifolia Scop. (5.7%). The northwestern slope had the highest species abundance (17 species), the largest value of Shannon-Weiner index (3.19 bits) and the smallest value of Simpson index (0.21) while the southwestern slope had the lowest species abundance (10.6 species), the smallest value of Shannon–Weiner index (2.36 bits) and the largest value of Simpson’s index (0.33). The similarity of plant types was highest between the plants of the northern and northwestern slopes (94.1%).